Gene editing and synthetically accessible inhibitors reveal role for TPC2 in HCC cell proliferation and tumor growth. Issue 8 (19th August 2021) - Müller, Martin; Gerndt, Susanne; Chao, Yu-Kai; Zisis, Themistoklis; Nguyen, Ong Nam Phuong; Gerwien, Aaron; Urban, Nicole; Müller, Christoph; Gegenfurtner, Florian A.; Geisslinger, Franz; Ortler, Carina; Chen, Cheng-Chang; et al.
Summary: The role of two-pore channel 2 (TPC2), one of the few cation channels localized on endolysosomal membranes, in cancer remains poorly understood. Here, we report that TPC2 knockout reduces proliferation of cancer cells in vitro, affects their energy metabolism, and successfully abrogates tumor growth in vivo . Concurrently, we have developed simplified analogs of the alkaloid tetrandrine as potent TPC2 inhibitors by screening a library of synthesized benzyltetrahydroisoquinoline derivatives. Removal of dispensable substructures of the lead molecule tetrandrine increases antiproliferative properties against cancer cells and impairs proangiogenic signaling of endothelial cells to a greater extent than tetrandrine. Simultaneously, toxic effects on non-cancerous cells are reduced, allowing in vivo administration and revealing a TPC2 inhibitor with antitumor efficacy in mice. Hence, our study unveils TPC2 as valid target for cancer therapy and provides easily accessible tetrandrine analogs as a promising option for effective pharmacological interference. Graphical abstract: Highlights: TPC2 knockout reduces HCC cell proliferation and prevents tumor growth TPC2 deficiency alters the metabolic phenotype Easily accessible, potent inhibitors with favorable drug-likeness were developed Abstract : Müller et al. describe that genetic TPC2 knockout reduces cell proliferation in vitro, alters cellular energy metabolism, and effectively suppresses tumor growth in vivo, suggesting that this lysosomal ion channel represents a suitable target for cancer therapy. Concurrently, a potent TPC2 inhibitor with antitumor efficacy was developed.